2010
DOI: 10.4067/s0718-95162010000200001
|View full text |Cite
|
Sign up to set email alerts
|

FORMATION OF POST-FIRE WATER-REPELLENT LAYERS IN MONTERREY PINE (pinus radiata D. DON) PLANTATIONS IN SOUTH-CENTRAL CHILE

Abstract: A wildfire burned about 15,000 ha of Monterrey Pine (Pinus radiata D. Don) plantations near Yungay, Chile, in January of 2007. Post-fire water repellency (hydrophobicity) was measured using the water-drop-penetration-time (WDPT) method at depths of 0, 5, and 10 mm from the soil surface. These measurements were collected on burned sites of both young (4-years old) and old (11-years old) plantations having both sand-and clay-rich soils. For purpose of comparison, water repellency was also measured one year after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…Steeper slopes (Hualo site) should result in the erosion of finer soil particles located on the surface, leading to a slightly coarser material on the soil-fire interacting range, compared to those from flatter areas (Pine site). Similar to what Garcia-Chevesich et al (2010) found on Chilean soils near Yungay (VIII Region), fine-textured surface soils from the PINE site probably prevented much of its volatilized water repellent substances from migrating very far below the surface during the fire (DeBano, 1981;Letey et al, 2000). This was, not the case for the possible surface (first two millimeters) coarser soils of the Hualo site, if that was the case before the fire occurred.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Steeper slopes (Hualo site) should result in the erosion of finer soil particles located on the surface, leading to a slightly coarser material on the soil-fire interacting range, compared to those from flatter areas (Pine site). Similar to what Garcia-Chevesich et al (2010) found on Chilean soils near Yungay (VIII Region), fine-textured surface soils from the PINE site probably prevented much of its volatilized water repellent substances from migrating very far below the surface during the fire (DeBano, 1981;Letey et al, 2000). This was, not the case for the possible surface (first two millimeters) coarser soils of the Hualo site, if that was the case before the fire occurred.…”
Section: Discussionsupporting
confidence: 58%
“…A drop of water was placed on the mineral soil surface (manually removing the remaining ashes, if any), documenting how long it took for the drop to infiltrate into the soil. The same criteria used by Garcia-Chevesich et al (2010), was applied to determine the degree of water repellency (originally from the US National Wildfire Coordinating Group), i.e., slight or null repellency (the drop of water takes 10 sec or less to infiltrate), moderate repellency (between 10 and 40 sec) and strong repellency (more than 40 sec).…”
Section: Methodsmentioning
confidence: 99%
“…Temperatures from 220-480˚C are known to convert biomass into a mixture of partially pyrolyzed organic compounds, while volatilized waxes and lipids typically condense at temperatures around 200˚C in the soil below [16]. This process results in a hydrophobic zone that commonly occur in forest fires and can lead to heavy erosion by channelizing runoff [17][18][19]. Thus, the upper layers of soil will have highly modified, fire-specific carbon sources that may select for specific sets of organisms able to metabolism them.…”
Section: Introductionmentioning
confidence: 99%
“…Soil water repellency is a common phenomenon that is observed postfire in Mediterranean forest soils but also in agricultural soils in which hydrophobic organic substances are produced during plant decomposition in rotations including legumes (Garcia-Chevesich, 2010;Casanova et al, 2013;Fuentes et al, 2015). Considering the thresholds for the water repellency index (R) as defined by Iovino et al (2018), all sites, particularly those with agroecological management, are included in the class of slight repellents (1.95≤R<10) at the soil surface (Supplemental Material 2), while at depth, the general trend changed to wettable soils (R<1.95).…”
Section: Resultsmentioning
confidence: 99%